A dimensão educativa do processo de participação popular na gestão pública local - Lima, Gisania Carla de (2009)
This study refers an analysis of educative dimension of common participation s process in local public administration, trying to comprehend the organization of the manners of social individual, the acting collective spaces and the educative actions developed in this conjecture. In this sense it was theoretical methodological reference that constitutes from literature about participation like a practice for individual s emancipation, common education like the methodology that supports this practice and to this end the relation of these two concepts in Common Participation of Pedagogy. Like procedure it was applied questionary and interviews with a semi ready outline that allowed us to approximate this real situation also a documental data. We perceive that educative dimension of common participation constitutes from articulator theme, that is the public estimate responsible for mobilization of civilization it results in creation of spaces of learning and consequently the mobilization of local public environment to dialogue about public politics. For this context are created collective learning very important in the process of participation of the exercise of popular power and consolidation of cultura participation in the city.